Recreating a medieval urban scene with virtual intelligent characters: steps to create the complete scenario - Ana Paula Cláudio; Maria Beatriz Carmo; Alexandre Antonio de Carvalho; Willian Xavier; Rui Filipe Antunes (Virtual Archaeology Review, 2017)
From historical advice to 3D modeling and programming, the process of reconstructing cultural heritage sites populated with virtual inhabitants is lengthy and expensive, and it requires a large set of skills and tools. These constraints make it increasingly difficult, however not unattainable, for small archaeological sites to build their own simulations. In this article, we describe our attempt to minimize this scenario. We describe a framework that makes use of free tools or campus licenses and integrates the curricular work of students in academia. We present the details of methods and tools used in the pipeline of the construction of the virtual simulation of the medieval village of Mértola in the south of Portugal. We report on: a) the development of a lightweight model of the village, including houses and terrain, and b) its integration in a game engine in order to c) include a virtual population of autonomous inhabitants in a simulation running in real-time.